Prospective evaluation of the learning curve and electrical characteristics of left bundle branch area pacing. (14th October 2021) - Heckman, L I B; Luermans, J G L M; Jastrzebski, M; Stipdonk, A M W; Westra, S; Weijs, B; Den Uijl, D; Linz, D; Mafi-Rad, M; Prinzen, F W; Vernooy, K
Abstract: Background: Left bundle branch area pacing (LBBAP) has recently been introduced as a physiological pacing technique with a synchronous ventricular activation. Objective: To prospectively evaluate the feasibility and learning curve, as well as the electrical characteristics of LBBAP. Methods: In 80 consecutive LBBAP pacemaker patients, ECG characteristics during intrinsic rhythm, RV septum pacing (RVSP) and LBBAP were evaluated. From the ECG's QRS duration and LVAT (stimulus to V6 R-wave peak time, RWPT) were measured. Also, the left bundle branch potential (LBBpot) to V6 RWPT interval was measured and compared to the LVAT. After conversion of the ECG into VCG (Kors conversion matrix), QRS area, as measurement for electrical dyssynchrony, was calculated. Results: Permanent lead implantation was successful in 77/80 patients (96%) undergoing an attempt at LBBAP. LBBAP lead implantation time as well as fluoroscopy time were significantly shorter during last 25% of implantation compared to first 25% of implantations (17±5 min vs. 33±16 min and 12±7 min vs. 21±13 min, respectively, panel A and B). LBB capture was obtained in 54/80 patients (68%). In 36/45 patients (80%) with intact AV conduction and narrow QRS an LBBpot was present. The mean interval between the LBBpot and the onset of QRS was 22±6 ms. In the patients with narrow QRS (n=45), QRS duration increased significantly during both RVSP (139±24 ms) and LBBAP (123±21 ms), compared to intrinsic rhythm (95±13 ms). QRS area on the other hand, increased during both RVSP (73±20 μVs) but decreased during LBBAP (41±15 μVs), to values close to intrinsic rhythm (32±16 μVs, panel C). For all patients, QRS area was significantly lower in patients with LBB capture compared to patients without capture (43±18 μVs vs 54±21 μVs, respectively). In patients with LBB capture (n=54), LVAT was significantly shorter compared to patients without LBB capture (75±14 vs. 88±9 ms, respectively). In the patients with LBB capture, there was a significant correlation between the LBBpot – V6 RWPT and S – V6 RWPT intervals (Pearson correlation 0.739, P<0.001). Conclusion: LBBAP is a safe and feasible technique, with a clear learning curve that seems obtained after ± 40–60 implantations. LBB capture is obtained in two-thirds of patients. Although QRS duration remains prolonged, LBBAP largely restores ventricular electrical synchrony to values close to intrinsic (narrow QRS) rhythm. Funding Acknowledgement: Type of funding sources: None.